2022
DOI: 10.1038/s41467-022-33267-z
|View full text |Cite
|
Sign up to set email alerts
|

A single arm phase Ib/II trial of first-line pembrolizumab, trastuzumab and chemotherapy for advanced HER2-positive gastric cancer

Abstract: In this multi-center phase II trial, we evaluated the efficacy and safety of a quadruplet regimen (pembrolizumab, trastuzumab, and doublet chemotherapy) as first-line therapy for unresectable or metastatic human epidermal growth factor receptor 2 (HER2)-positive advanced gastric cancer (AGC) (NCT02901301). The primary endpoints were recommended phase 2 dose (RP2D) for phase Ib and objective response rate (ORR) for phase II. The secondary endpoints included progression-free survival (PFS), overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Our study demonstrated the panel's reliable accuracy and sensitivity in detecting genetic alterations, CNVs, EBV/HPV infections, and MSI status. Furthermore, we have recently reported translational data utilizing the CancerMaster for comprehensive genomic pro ling in solid tumors, providing further evidence of its signi cant clinical implications and further highlighting that it has potential to improve patient outcomes through personalized cancer treatment (C. K. Lee et al 2022). The panel's asynchronous and parallel analysis pipeline offers a seamless, one-stop solution for comprehensive and rapid reporting of clinically actionable variants while conserving limited tumor tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Our study demonstrated the panel's reliable accuracy and sensitivity in detecting genetic alterations, CNVs, EBV/HPV infections, and MSI status. Furthermore, we have recently reported translational data utilizing the CancerMaster for comprehensive genomic pro ling in solid tumors, providing further evidence of its signi cant clinical implications and further highlighting that it has potential to improve patient outcomes through personalized cancer treatment (C. K. Lee et al 2022). The panel's asynchronous and parallel analysis pipeline offers a seamless, one-stop solution for comprehensive and rapid reporting of clinically actionable variants while conserving limited tumor tissue.…”
Section: Discussionmentioning
confidence: 95%
“…The mPFS was 8.6 months and mOS achieved 19.3 months. At the same time, they explored the molecular signatures of enrolled patients, and next-generation sequencing indicated that RTK/RAS pathway alterations were closely correlated with PFS ( 32 ). In our study, the OS of patients with HER2 FISH positive was different in two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific rationale for using this triple combination is to facilitate tumor responses via tumor targeting through cross-priming, chemotherapy-induced immunogenic cell death, or modification of the immunosuppressive microenvironment. Proof-of-concept data from two single-arm phase II trials of pembrolizumab in combination with chemotherapy plus trastuzumab have been reported [ 76 77 ]. Janjigian et al [ 76 ] reported an ORR of 91% (95% CI, 78–97), 13 months of PFS (95%CI, 8.6–not reached [NR]), and 27.3 months of OS (95% CI, 18.8–NR).…”
Section: Chemotherapy-based Triple Combinationmentioning
confidence: 99%
“…PFS was associated with HER2 plasma copy number but not with tissue HER2 copy number, suggesting that plasma copy number better reflected tumor heterogeneity. The PANTHERA trial ( NCT02901301 ) [ 77 ] reported a 95% tumor shrinkage rate and an ORR of 77% (95% CI, 61.4–88.2) with a PFS of 8.6 (95% CI, 7.2–16.4) and an OS of 19.3 (95% CI, 16.5–NR) months. Patients with HER2 amplification had longer PFS than patients without amplification (22.0 vs. 7.6 months: HR, 0.28; P=0.01).…”
Section: Chemotherapy-based Triple Combinationmentioning
confidence: 99%